A novel biomagnetic method to study gastric antral contractions - Miranda, JRA; Oliveira, R. B.; Sousa, P. L.; Braga, FJH; Baffa, O. (Iop Publishing Ltd, 1997)
A novel non-invasive method to study the motion associated with gastric antral contractions is discussed. The method is based on magnetic flux changes detected by an a.c. biosusceptometer, produced by a magnetic test meal within the stomach. Measurements are made at the surface of the torso and are easy to perform. Simultaneous measurements were made with electrogastrography and scintigraphy showing remarkable coincidence. The effect of a drug on the amplitude of antral contractions was also assayed with the new method.